Optimal Distributed Generation and Reactive Power Allocation in Electrical Distribution Systems - Pereira, Benvindo R.; Martins da Costa, Geraldo R.; Contreras, Javier; Sanches Mantovani, Jose R. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
Optimal and simultaneous siting and sizing of distributed generators and capacitor banks in distribution systems have attracted a lot of attention from distribution companies. The placement and capacity of these devices have direct effects on the system's performance. This paper presents a model for the simultaneous allocation of capacitor banks and distributed generation, which takes into account the stochastic nature of distributed generation. To solve the model presented, we propose an efficient hybrid method based on Tabu search and genetic algorithms. The hybrid method is applied to a well-known system in literature.
Keywords: Capacitor bank (CB); distributed generation (DG); uncertainty; Tabu search (TB); Chu-Beasley genetic algorithm (CBGA)